2015
DOI: 10.3109/00016489.2015.1012276
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of programmed cell death signaling in hair cells and support cells post-electrode insertion trauma

Abstract: At 6 h post-EIT the SCs immunolabeled for the presence of phosphorylated-Jun and activated caspase-3. Phosphorylated p-Jun labeling was observed at 12 h in both the HCs and SCs of middle and basal cochlear turns. Cleaved caspase-3 was not observed in HCs of any cochlear turn at up to 24 h post-EIT. Lipid peroxidation (HNE immunostaining) was first observed at 12 h post-EIT in both the HCs and SCs of the basal turn, and reached the apical turn by 24 h post-EIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 11 publications
1
42
0
2
Order By: Relevance
“…Correlations between spiral ganglion neuron loss and the degree of inflammation responses have been observed (e.g. Xu et al 1997; Fayad et al 2009), which is consistent with the suggestion that an inflammatory response also may be toxic to the neurosensory structures in the cochlea (Bas et al 2015; Eshraghi et al 2015). A hypersensitivity reaction to the electrode array may be more common than originally thought (e.g.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Correlations between spiral ganglion neuron loss and the degree of inflammation responses have been observed (e.g. Xu et al 1997; Fayad et al 2009), which is consistent with the suggestion that an inflammatory response also may be toxic to the neurosensory structures in the cochlea (Bas et al 2015; Eshraghi et al 2015). A hypersensitivity reaction to the electrode array may be more common than originally thought (e.g.…”
Section: Introductionsupporting
confidence: 86%
“…Reduced movement in apical cochlear regions, which would decrease the ear’s sensitivity to low-frequency stimuli, could occur when fibrotic tissue invades the scala tympani (Choi and Oghalai 2005). Moreover, the biological processes responsible for the fibrotic tissue may be toxic to the neurosensory structures of the inner ear (Bas et al 2015; Eshraghi et al 2015), which could also account for a decrease in acoustic hearing. Significant correlations between the degree of tissue reaction and the amount of acoustic hearing loss have been observed in animals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown relatively poor correlations of hearing loss with hair cell and/or spiral ganglion cell loss in guinea pigs (Tanaka et al 2014; O’Leary et al 2013). Other studies have shown that electrode insertion trauma can result in programmed cell death in cochlear structures (Eshraghi et al, 2013, 2015). Finally, post-implant fibrosis due to electrode insertion may have an effect on cochlear mechanical responses to sound (Choi and Oghalai 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In this setting, preservation of residual hearing has become a clinical priority, and mechanisms by which this goal can be accomplished have become an area of intense focus. This is particularly challenging because direct tissue trauma from CI electrode insertion can trigger the caspase pathway and programmed cell death in hair cells, resulting in additional loss of residual hearing . Cochlear SCs have been shown to support the survival of both spiral ganglion neurons and cochlear hair cells .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly challenging because direct tissue trauma from CI electrode insertion can trigger the caspase pathway and programmed cell death in hair cells, resulting in additional loss of residual hearing. 14 Cochlear SCs have been shown to support the survival of both spiral ganglion neurons and cochlear hair cells. 15 Thus, the finding of surviving SCs after CI has several clinically significant implications: 1) the presence of a CI may not preclude patients from future attempts at regenerating hair cells from SCs; and 2) SCs can continue their normal function of maintaining cochlear structure, promoting hair cell fate and supporting spiral ganglion cell survival.…”
Section: Discussionmentioning
confidence: 99%